A Review of Training Strategies to Teach Individuals Implementation of Behavioral Interventions. Issue 1 (2nd January 2017) - Shapiro, Marnie; Kazemi, Ellie
ABSTRACT: The purpose of this review is to provide a critical analysis of research on staff training procedures to identify best practices as well as unanswered questions, which may be addressed in future research. We analyzed 24 articles along the dimensions of participant and intervention characteristics; the procedures targeted for training, training components, and mediums of delivery; the duration of training and the effectiveness of the outcomes; the generality; and the social validity of the training strategies. We discussed the implication of the findings as they relate to research and practice.